DEVELOPING A COMPREHENSIVE RISK MANAGEMENT MODEL FOR INTEGRATED ELECTRICITY PROVIDERS: INSIGHTS FROM ISO 22301-BASED FINANCIAL IMPACT ANALYSIS - Sutarmin, Sutarmin; Fitriani, Lisa (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
This study explores financial resilience strategies for integrated electricity service providers in navigating global turbulence, including regulatory pressures and energy transition, cyber threats, exchange rate volatility, and disruptions in primary energy supply chains. The analysis integrates the Risk Maturity Index (RMI) and Business Impact Analysis (BIA) based on ISO 22301 standards—commonly applied to operational aspects, but in this study extended to financial dimensions. The research employs a mixed approach: quantitative descriptive methods and qualitative inquiry through case studies, interviews, observations, document analysis, stress testing, risk heat mapping, and scenario sensitivity testing. The findings indicate that the company remains at a low level of risk maturity (RMI 2.4 – developing phase) and faces significant strategic risks in liquidity, tariff setting, infrastructure reliability, and cybersecurity. Applying financial BIA provides a clearer risk landscape, identifies crisis triggers, and formulates recovery strategies that enhance business continuity capabilities. The study recommends strengthening asset management, improving human resource capacity, and exploring financial instruments for risk mitigation. Overall, these findings contribute to the development of a comprehensive risk management model that is particularly relevant for strategic public service enterprises.